Problem issues regarding land planning in conditions of decentralization - Andriyash, Victoria; Еvtushenko, Alexander; Lushahina, Tetyana; Lininska, Oksana (Public Administration and Regional Development, 2021)
The article considers theoretical issues of regulatory and legal regulation of land relations in the field of public administration. It is emphasized that the analysis and assessment of the current legal situation in land use is evidence not only of its extreme severity, especially after the adoption of the law on land sales, but also of the unresolved many problems of an administrative nature. The peculiarities of the prospects of practical implementation of the legislative framework of land relations, formulated as various acts and programs of different levels, which face a number of problems in the field of law, governance and land reform policy in decentralization, which requires a clear definition of the essence and content of basic concepts. land relations in the field of management. The issues of the main forms of land planning of united territorial communities in the conditions of decentralization are studied. It is emphasized that the science of public administration acquires the status of a productive force that can make a significant contribution to the development of domestic land relations of the market type, ensure a high level of efficiency of economic entities, consolidate, integrate and organize regulatory behavior of all participants in land relations. Decomposing the above into certain aspects, the general conclusion is that the decentralization of power introduced in Ukraine and deregulation of business stimulates changes in all spheres of life of rural, urban, urban communities, which are in the process of unification into a single territorial community. Analysis of the legislation on land and territory planning shows the difference in legal relations for the formation, approval and application of urban planning documentation against the background of legal regulation of land relations. And they miss the issue of taking into account the needs and interests of the newly created administrative units, united territorial communities as new subjects of communal land ownership.